Declining correspondent banking relationship in the West African Monetary Zone - Ngozi Eunice Egbuna; Abdoulaye Barry; Eric Adjapong; George Okorie; Oyebanji Joel Olaoye; Augustine Ujunwa; Rita Ntim Fosu; Omar Sherif; Amadou Diallo; Augustine Sao Ngombu (West African Monetary Institute (WAMI), 2021)
Declining correspondence banking relationship was a major feature of the banking industry in the Member States of the West African Monetary Zone WAMZ from 2013 to 2016. This objective of this study, therefore, was to clarify our understanding of the drivers of declining corresponding banking relation in the WAMZ. To achieve this objective, we explored the main sources of de-risking in (WAMZ), using questionnaires administered to commercial banks. We document perceived antimoney laundering/combating the financing of terrorism (AML/CFT) concerns and commercial consideration on the part of correspondent banks as the main drivers of de-risking in the WAMZ. Other causes of de-risking include: high compliance and additional requirements demanded by correspondent banks in reflection of an upscale in the legal, regulatory and supervisory requirements in their (correspondent bank's) jurisdictions; lack of full compliance with pre-existing legal, supervisory and regulatory requirements by foreign financial institutions; barriers or bureaucratic nature of communication and information sharing, low level of disclosure on customers, low sovereign credit risk rating and low level of profitability of CBR services. In terms of impact, we noted that the phenomenon affected banks to carry out international wire transfer and some critical banking and money transfer services. The study recommends the need to strengthen existing regulatory and supervisory frameworks, in particular the AML/CFT regime in the Zone.
Keywords: G15; G21; G32; 330; De-risking; correspondent banking relationship; WAMZ; Anti-money laundering; regression analysis; mutual evaluation exercise